Identification and integrative analysis of microRNAs in myelodysplastic syndromes based on microRNAs expression profile. Issue 4 (1st February 2022) - Ma, Limin; Yang, Haiping; Yang, Xuewen
Abstract: Myelodysplastic syndromes (MDS) are a group of malignant hematological disorders characterized by the abnormal development of hematopoietic stem cells and increased risk of acute myelogenous leukemia. Although the pathogenesis of MDS has not been fully understood, various alterations of microRNAs (miRNAs) have been reported in MDS. This study aimed to explore the molecular mechanisms of MDS by integrative bioinformatics analysis of miRNAs expression profile. The GSE81372 expression profile dataset was downloaded from Gene Expression Omnibus database. The differentially expressed miRNAs (DEMs) between MDS and normal controls were identified and targets of miRNAs were predicted. Subsequently, gene ontology (GO) functional and pathway enrichment analyses of target genes were performed. Finally, pathway relation network and miRNA–GO regulatory network were constructed and analyzed. A total of six upregulated and 35 downregulated DEMs were identified. The results showed that target genes of DEMs mainly participated in the process of signal transduction, blood coagulation, apoptotic process, cell proliferation, transmembrane transport, and angiogenesis. The significantly enriched pathways included MAPK signaling pathway, PI3K‐Akt signaling pathway, TGF‐beta signaling pathway, Hippo signaling pathway, and P53 signaling pathway. Moreover, miR‐195‐5p, miR‐4505, miR‐22‐3p, and miR‐148a‐3p were selected as hub miRNAs in miRNA–GO regulatory network and their aberrant expression might be closely associated with MDS pathogenesis. Our discovery provides a registry of miRNAs and pathways that are disrupted in MDS, which has the potential to be used in clinic for diagnosis and target therapy of MDS in future. Abstract : miR‐195‐5p, miR‐4505, miR‐22‐3p and miR‐148a‐3p were selected as hub microRNAs in microRNA‐Gene ontology regulatory network and their aberrant expression might be closely associated with myelodysplastic syndromes pathogenesis. Their target genes mainly participated in the process of signal transduction, blood coagulation, apoptotic process, cell proliferation, transmembrane transport and angiogenesis